2018
DOI: 10.1186/s12936-018-2223-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo validation of anti-malarial activity of crude extracts of Terminalia macroptera, a Malian medicinal plant

Abstract: BackgroundPlasmodium falciparum malaria is still one of the most deadly pathology worldwide. Efficient treatment is jeopardized by parasite resistance to artemisinin and its derivatives, and by poor access to treatment in endemic regions. Anti-malarial traditional remedies still offer new tracks for identifying promising antiplasmodial molecules, and a way to ensure that all people have access to care. The present study aims to validate the traditional use of Terminalia macroptera, a Malian plant used in tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 39 publications
(39 reference statements)
8
29
0
Order By: Relevance
“…Both extracts of the plant prolonged the mean survival time of the experimental mice indicating that the plant suppressed P. berghei and reduced the overall pathologic effect of the parasite on mice. Similar result on mean survival time of mice was reported in studies conducted on T. chebula, T. bellerica [31], and T. macroptera [32].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both extracts of the plant prolonged the mean survival time of the experimental mice indicating that the plant suppressed P. berghei and reduced the overall pathologic effect of the parasite on mice. Similar result on mean survival time of mice was reported in studies conducted on T. chebula, T. bellerica [31], and T. macroptera [32].…”
Section: Discussionsupporting
confidence: 89%
“…Based on the above classification, the plant is considered to have exhibited a good antiplasmodial activity. is assertion is evidenced by other in vivo studies that reported antimalarial activity of other species of the same genus such as T. chebula, T. bellerica [31], and T. macroptera [32].…”
Section: Discussionmentioning
confidence: 65%
“…At present, the following chemical labelling and classification of acute systemic toxicity, based on oral LD 50 values, are from the recommendations of the Globally Harmonized System of Classification [OECD, 2008], and ranked as: very toxic, ≤ 5 mg/kg; toxic, > 5 ≤ 50 mg/kg; harmful, > 50 ≤ 500 mg/kg; and no label, > 500 ≤ 2000 mg/ kg [4]. In our previous work [3], oral administration of TML and TMR at a dose of 2000 mg/kg did not cause mortality among experimental animals. This indicates that the LD 50 s of TML and TMR are…”
Section: Resultsmentioning
confidence: 99%
“…2 Ten samples as sold. 3 Registration form of the manufacturer and memoranda of understanding between the manufacturer and a research institution. 4 Complete monograph(s) of the plant's component(s).…”
Section: Requested Items For Marketing Authorization Deliverymentioning
confidence: 99%
See 1 more Smart Citation